2014
DOI: 10.3329/bjar.v39i1.20149
|View full text |Cite
|
Sign up to set email alerts
|

Adoption of mungbean technologies and technical efficiency of mungbean (Vigna radiata) farmers in selected areas of Bangladesh

Abstract: Mungbean is one of the most important pulse crops in Bangladesh. The demand of mungbean is very high due to its good taste. To date, different national institutes released 14 improve mungbean varieties with complete package of technologies and disseminated them to the farmers. But, the farm level adoption of mungbean varieties, their economics, and farmer’s efficiencies are not well known to the researchers and policy planners. Therefore, the study assessed the farm level adoption of mungbean technologies, tec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
9
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 6 publications
3
9
1
Order By: Relevance
“…variation which is similar to the findings of other studies [24,48]. Under the conventional SFPF model, the mean technical efficiency (MTE) was similar for both groups of farmers (Figure 1).…”
Section: Technical Efficiency Distributionsupporting
confidence: 90%
“…variation which is similar to the findings of other studies [24,48]. Under the conventional SFPF model, the mean technical efficiency (MTE) was similar for both groups of farmers (Figure 1).…”
Section: Technical Efficiency Distributionsupporting
confidence: 90%
“…A limited number of studies exist on the adoption of improved varieties, profitability and/or production performance of pulses in Bangladesh with varied conclusions. For example, Miah et al [22] noted that 44% of the sampled farmers had adopted improved pulses while Sarker [23] and Haque et al [24] noted that 100% of sampled farmers had adopted improved varieties of lentil and mungbean, respectively. Lack of good quality seed as well as pest and disease infestation were identified as the main constraints in adopting improved varieties of pulses [22,24].…”
Section: Introductionmentioning
confidence: 99%
“…For example, Miah et al [22] noted that 44% of the sampled farmers had adopted improved pulses while Sarker [23] and Haque et al [24] noted that 100% of sampled farmers had adopted improved varieties of lentil and mungbean, respectively. Lack of good quality seed as well as pest and disease infestation were identified as the main constraints in adopting improved varieties of pulses [22,24]. Similarly, Islam et al [25] reported 35% higher profit for improved varieties of blackgram, Islam and Ali [26] estimated a Benefit Cost Ratio (BCR) of 1.80 for improved varieties of lentil whereas Islam et al [25] and Haque et al [24] reported BCRs of 2.35 and 1.69 for improved varieties of mungbean, respectively.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations